2006
DOI: 10.1063/1.2176334
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic resonance study of the exchange bias field in NiFe∕FeMn∕NiFe trilayers

Abstract: The ferromagnetic resonance (FMR) technique is used to study the exchange bias field in asymmetrical NiFe∕FeMn∕NiFe trilayers produced by dc magnetron sputtering under different working pressures. The FMR spectra give evidence of two resonance modes attributed to the two asymmetrical noninteracting NiFe layers. The study of the in-plane angular dependence of the absorption field allows the measurement of the exchange bias field at both bottom ferromagnetic (FM)∕antiferromagnetic (AFM) and top AFM∕FM interfaces. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…Thus, the most probably explanation is the reason (ii), i.e., the atomic diffusion has a strong contribution to the s values of the NiFe/FeMn interfaces. The evidence of atomic diffusion at the NiFe/FeMn interfaces was also found by ferromagnetic resonance results [19] (not shown here) which confirmed that the upper AF/FM interface are less homogeneous than the lower one probably due to an atomic diffusion at the AF/FM interfaces (stronger in the upper interface).…”
Section: Discussion and Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, the most probably explanation is the reason (ii), i.e., the atomic diffusion has a strong contribution to the s values of the NiFe/FeMn interfaces. The evidence of atomic diffusion at the NiFe/FeMn interfaces was also found by ferromagnetic resonance results [19] (not shown here) which confirmed that the upper AF/FM interface are less homogeneous than the lower one probably due to an atomic diffusion at the AF/FM interfaces (stronger in the upper interface).…”
Section: Discussion and Resultssupporting
confidence: 88%
“…However, when one layer is deposited subsequently on the other, it favors the diffusion of Ni and Mn atoms at the interface, since the associated heat of mixing is more negative (DH mix = À8 kJ/ mol) [37]. The evidence that an increasement in the argon working pressure enhances the atomic diffusion at the interface is also corroborated by ferromagnetic resonance measurements [19] and Mössbauer spectroscopy results (not shown here). The increase of the argon working pressure could also induce other structural effects like changes in grain size, that can contribute to the enhancement of the s values of the NiFe/FeMn interfaces, i.e., if the growth of the NiFe and FeMn layers are not columnar, changes in grain size could also produce modifications in the interfacial roughness.…”
Section: Discussion and Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Since materials used for spintronics are either ferromagnetic or spin correlated, and FMR is not only employed to study their magneto static behaviors, for instances, anisotropies [1,2], exchange coupling [3,4,5,6], but also the spin dynamics; such as the damping constant [7,8,9], g factor [8,9], spin relaxation [9], etc. In this chapter a brief description about the key components and techniques of FMR will be given.…”
Section: Introductionmentioning
confidence: 99%